Long-term outcomes of radiofrequency ablation vs. partial nephrectomy for cT1 renal cancer: A meta-analysis and systematic review - Li, Linjin; Zhu, Jianlong; Shao, Huan; Huang, Laijian; Wang, Xiaoting; Bao, Wenshuo; Sheng, Tao; Chen, Dake; He, Yanmei; Song, Baolin (Frontiers in Surgery, 2023)
Background: Partial nephrectomy (PN) is one of the most preferred nephron-sparing treatments for clinical T1 (cT1) renal cancer, while radiofrequency ablation (RFA) is usually used for patients who are poor surgical candidates. The long-term oncologic outcomes of RFA versus PN for cT1 renal cancer remains undetermined. This meta-analysis aims to compare the treatment efficacy and safety of RFA and PN for patients with cT1 renal cancer with long-term follow-up of at least 5 years. Method: This meta-analysis was performed following the PRISMA reporting guideline. Literatures that had data on the comparison of the efficacy or safety of RFA versus PN in treating cT1 renal cancer were searched in databases including PubMed, Embase, Web of Science and the Cochrane Library from Jan 1, 2000 to May 1, 2022. Only long-term studies with median/mean follow-up of at least 5 years were included. The following measures of effect were pooled: odds ratio (OR) for recurrence and major complication; hazard ratio (HR) for progression free survival (PFS), cancer-specific survival (CSS) and overall survival (OS). Additional analysis including sensitivity analysis, subgroup analysis and publication bias analysis were also performed. Results: A total of 7 studies with 1962 patients were finally included. The treatment efficacy of RFA was not different with PN in terms of cancer recurrence (OR=1.22, 95%CI=0.45-3.28), PFS (HR=1.26, 95%CI=0.75-2.11) and CSS (HR=1.27, 95%CI=0.41-3.95) as well as major complication (OR=1.31, 95%CI=0.55-3.14)(P>0.05 for all). RFA was a potential significant risk factor for OS(HR=1.76, 95%CI=1.32-2.34, P<0.001). No significant heterogeneity and publication bias were observed. Conclusion: This is the first meta-analysis that focuses on the long-term oncological outcomes of cT1 renal cancer, and the results suggest that RFA has comparable therapeutic efficacy to PN. RFA is a nephron-sparing technique with favorable oncologically efficacy and safety and a good treatment alternative for cT1 renal cancer.